Aspects of the structure and function of some gastropod columellar muscles (Mollusca) - Frescura, Mandy (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1991)
The columellar muscle of both limpets and coiled shell gastropods is of the paramyosin smooth type. Collagen forms an integral part of the musculature constituting about 35% of the tissue. In limpets, muscle organisation is typical of a muscular hydrostat. Tightly packed blocks of muscle, dense arrays of cross-linked collagen, large muscle cells (9 µm diameter) and thick filaments (70 nm diameter, 30 µm long) produce a tough, relatively rigid but powerful muscle. In coiled shell gastropods, muscle organisation is intermediate between a muscular and a fluid hydrostat. Finer muscle cells (6 µm diameter), thick filaments (60 nm diameter) and a loose intercellular network of collagen interspersed with fluid vesicles are features of a more pliable and extensible muscle. In addition, ultrastructural differences, such as larger numbers of mitochondria and sarcolemmal invaginations distinguish the tarsal from the columellar muscle in both limpets and coiled shell gastropods. About 25% of muscle cells in most species examined, contain a novel arrangement of thin filaments with periodic electron-dense regions. These are similar in appearance to intrafusal cells and stress-fibres of non-muscle cells. Structural analysis of isolated filaments, optical diffraction and SDS gel electrophoresis confirm the, large dimensions and the paramyosin nature of the thick filaments. Microdensitometry of the gel proteins confirms the high proportion of collagen present. No significant differences in muscle ultrastructure were found between limpets from different tidal heights. Muscle attachment areas are shown to be species-specific and positively correlated to tenacity and wave exposure. The muscle attachment mechanism is similar to that described for other molluscs. It consists of a special epithelial layer and a mucous-like material at the muscle-shell interface that possibly has an adhesive function. Although the ultrastructure of Patella is very similar to that of the anterior byssus retractor of Mytilus, its mechanical behaviour is not. The muscle has a narrow working range where maximum tensions and "catch-like" contractions develop. This narrow length range is co-incident with the in situ length at which clamping occurs. It is suggested that the large component of collagen has an important influence over the mechanical behaviour of the muscle during clamping, by cross-linking in a manner similar to that described for some echinoderm connective tissues.
Keywords: Gastropoda -- Research Mollusks -- Research